Manipulating Cherenkov Radiation and Smith–Purcell Radiation by Artificial Structures. Issue 14 (1st April 2019) - Su, Zhaoxian; Xiong, Bo; Xu, Yihao; Cai, Ziqiang; Yin, Jianbo; Peng, Ruwen; Liu, Yongmin
Abstract: A moving charged particle, such as an electron, can radiate light due to the interaction between its Coulomb field and surrounding matter. This phenomenon has spawned great interest in the fields of physics, electron microscopy, optics, biology, and materials science. Since the radiation generated by the charged particles strongly depends on the surrounding matter, artificially engineered materials with exotic electromagnetic and optic properties, including metamaterials and metasurfaces, provide an unprecedented opportunity to tailor the interaction between the charged particle and matter, and ultimately enable to manipulate the radiated light. In this review, the fundamentals of Cherenkov radiation and Smith–Purcell radiation are presented. Subsequently, the recent advances in the control of Cherenkov radiation and Smith–Purcell radiation based on metamaterials and metasurfaces are summarized. Finally, the applications using these two physical phenomena, including electron‐driven photon sources and electron accelerators, are discussed in this review. Abstract : Artificially engineered materials, such as metamaterials and metasurfaces, offer new degrees of freedom to tailor the emission of charged particles in an unprecedented manner. This review summarizes the recent progress of manipulating Cherenkov radiation and Smith–Purcell radiation by artificial structures, discusses the relevant applications, and provides an outlook for this emerging research area.